RE-EXAMINING THE CULTURAL POLITICS AND THE MARATHI AND NON-MARATHI DIVIDE IN CONTEMPORARY MARATHI CINEMA - Narsing, Balande Chandoba (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Marathi films serve as a cultural battleground, mirroring the socio-political dynamics between Marathi and non-Marathi communities in Mumbai, Maharashtra’s economic capital. This paper examines how Marathi films like Mi Shivaji Raje Bhosale Boltoy (2009), Arjun (2011), and Balkadu (2015) address the perceived marginalization of Marathi people in Mumbai. The films project a complex narrative of displacement, focusing on the effects of migration, socio-economic disparities, and the erosion of Marathi identity. Central to this analysis are themes of cultural consciousness, business stereotypes, and emotional ties that Marathi people hold to Mumbai as both a geographical and symbolic space. Through each film, the conflict is explored between the local ‘Marathi Manoos’ and non-Marathi settlers, particularly those from Gujarat, who are often portrayed as the economic elites in the city. This paper aims to study how the characters in the films are depicted to challenge stereotypes to maintain their dignity and cultural identity, presenting a discourse on regional pride. Ultimately, this study asserts that these films contribute to a larger Marathi socio-political revival by addressing issues of economic displacement, cultural assimilation, and community solidarity. However, these narratives also risk falling into propagandistic tropes, promoting an ‘us vs. them’ mentality. This paper explores whether these films succeed in providing the fine line between cultural commentary and political propaganda.